2004
DOI: 10.1111/j.0956-7976.2004.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

The Correlates and Consequences of Newspaper Reports of Research on Sex Differences

Abstract: Correlates and consequences of newspaper accounts of research on sex differences were examined. In Study 1, articles from high-circulation newspapers were coded for the degree to which biological factors were used to explain sex differences. Results showed that political conservatism and traditional attitudes toward gender roles coded from other newspaper sections predicted greater use of biological explanations than did political liberalism and less traditional attitudes toward gender roles. In Studies 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(193 citation statements)
references
References 15 publications
3
183
2
5
Order By: Relevance
“…However, there is evidence that accounts of gender that emphasise biological factors leave us more inclined to agree with gender stereotypes, to selfstereotype ourselves, and for our performance to fall in line with those stereotypes (e.g., [2,7,8]). Moreover, other research from the social psychological literature has shown that presenting cognitive or emotional tasks in ways that make them seem diagnostic of gender tends to set up a self-fulfilling prophecy (e.g., [3,14,15,[21][22][23][24]).…”
Section: Meet Sarahmentioning
confidence: 99%
“…However, there is evidence that accounts of gender that emphasise biological factors leave us more inclined to agree with gender stereotypes, to selfstereotype ourselves, and for our performance to fall in line with those stereotypes (e.g., [2,7,8]). Moreover, other research from the social psychological literature has shown that presenting cognitive or emotional tasks in ways that make them seem diagnostic of gender tends to set up a self-fulfilling prophecy (e.g., [3,14,15,[21][22][23][24]).…”
Section: Meet Sarahmentioning
confidence: 99%
“…Reports of sex differences can influence beliefs and expectations of gender stereotypes (Brescoll & LaFrance, 2004). Despite the fact that empirical reports of sex differences are predominantly attributed to a limited number of skills, particularly specific higher order tasks observed in later school years or adulthood (e.g., Hyde et al, 1990a;Pratarelli & Steitz, 1995), discussion of sex differences in the media and lay publications may inappropriately lead to expectations for observable sex differences in the context of daily primary school activities.…”
Section: Introductionmentioning
confidence: 99%
“…Biological explanations of gender stereotypes can strengthen gender stereotypes (Brescoll & LaFrance, 2004), but androcentric explanations explicitly link women's attributes to gender status more than they do for men, such that women will bear the brunt of such stereotyping. Indeed, essentialist ideas are selectively used to explain stereotype-consistent sexual orientation differences, but such explanations focus on lesbians and gay men, and not on heterosexual women and men (Hegarty & Pratto, 2001.…”
mentioning
confidence: 99%